Targeting cGAS-STING: modulating the immune landscape of hepatic diseases - Xue, Feng; Liu, Yong-Kang; Chen, Xiao-Ying; Chen, Shan-Shan; Yu, Xiang-Rong; Li, Hua-Wen; Lu, Li-Gong; Chen, Mu-He (Frontiers in Immunology, 2025)
Liver diseases, including viral hepatitis, alcoholic liver disease (ALD), metabolic dysfunction-associated steatotic liver disease (MASLD), and hepatocellular carcinoma (HCC), represent a significant threat to global health due to their high mortality rates. The cGAS-STING pathway, a critical part of the innate immune system, plays a crucial role in detecting cytoplasmic DNA and initiating immune responses, including autoimmune inflammation and antitumor immunity. Genomic instability during cancer progression can trigger this pathway by releasing DNA into the cytoplasm. Emerging research indicates that cGAS-STING signaling is intricately involved in maintaining liver homeostasis and contributes to the pathogenesis of various liver diseases. This review outlines the cGAS-STING pathway, with a particular focus on its activation mechanism and its roles in several notable liver conditions. Specifically, we explore the complex interplay of cGAS-STING signaling in viral hepatitis, ALD, MASLD, and HCC, and discuss its potential as a therapeutic target. For example, in HCC, strategies targeting cGAS-STING include using nanomaterials to deliver STING agonists, combining radiofrequency ablation (RFA) with cGAS-STING activation, and leveraging radiotherapy to enhance pathway activation. Furthermore, modulating cGAS-STING activity may offer therapeutic avenues for viral hepatitis and chronic liver diseases like MASLD and ALD, either by boosting antiviral responses or mitigating inflammation. This review highlights the complex role of cGAS-STING signaling in these specific liver diseases and underscores the need for further research to fully realize its therapeutic potential.